CRISPR–Cas9 mediated gene therapy in inherited bone marrow failure syndromes - Munugoda Hewa, Nadeesha J. S.; KC, Rajendra; Hewitt, Alex W.; Fairfax, Kirsten A. (Frontiers in Hematology, 2025)
IntroductionThis systematic review evaluates CRISPR–Cas9 mediated gene therapy for inherited bone marrow failure syndromes, a heterogeneous group of rare inherited disorders characterised by cytopenia, cancer predisposition, and multi-organ involvement, for which supportive care and allogeneic haematopoietic stem cell transplantation provide cures for some but remain imperfect, donor-limited, and associated with significant morbidity. The objective of this review is to evaluate the current state of CRISPR–Cas9 mediated gene therapy in inherited bone marrow failure syndromes, with a focus on how this technology has been applied in experimental models to correct pathogenic mutations and restore haematopoietic function.MethodsWe searched PubMed, Scopus, and Google Scholar for studies combining inherited bone marrow failure syndromes with gene editing, prime editing, base editing, or CRISPR–Cas9.ResultsOf 876 records screened, 18 met the inclusion criteria. Fanconi anaemia predominated (n=8), with additional work in severe congenital neutropenia (n=3), Shwachman–Diamond syndrome (n=2), Diamond–Blackfan anaemia (n=2), and single studies in dyskeratosis congenita, congenital amegakaryocytic thrombocytopenia, and myelodysplastic syndrome/ acute myeloid leukaemia predisposition.DiscussionOverall, CRISPR–Cas9 has demonstrated feasibility for ex vivo correction in inherited bone marrow failure syndromes; however, future clinical adaptation will depend on overcoming key hurdles, such as careful assessment of off-target effects and establishing regulatory pathways that enable access for patients with rare diseases, thereby bridging the gap between preclinical and therapeutic application.